2017
DOI: 10.3389/fmicb.2017.00917
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Characteristics of Staphylococcus aureus Endovascular Infection Isolates from Different Clonal Complexes

Abstract: Staphylococcus aureus is a major cause of bacteremia and, even with appropriate clinical management, causes high morbidity, and mortality due to its involvement in endovascular complications and metastatic infections. Through different pathogenic in vivo and in vitro models we investigated the behavior of S. aureus most relevant clonal complexes (CCs) causing endovascular complications. We analyzed 14 S. aureus strains representing CC5, CC8, CC15, CC30, and CC45 that caused endovascular complications, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 43 publications
5
28
0
1
Order By: Relevance
“…24 The increasing number of hospital-acquired infections, especially BSI due to Staphylococcus spp., in recent years is closely linked to the spread of the mecA gene in strains living in hospital environment, which facilitates their ability to survive there. 4,6 In the present study, mecA was detected in 77.9% of the growth-positive blood cultures with staphylococcal isolates. Accordingly, bacteriemia with staphylococcal etiology is complicated by the emergence of methicillin-resistant pathogens.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…24 The increasing number of hospital-acquired infections, especially BSI due to Staphylococcus spp., in recent years is closely linked to the spread of the mecA gene in strains living in hospital environment, which facilitates their ability to survive there. 4,6 In the present study, mecA was detected in 77.9% of the growth-positive blood cultures with staphylococcal isolates. Accordingly, bacteriemia with staphylococcal etiology is complicated by the emergence of methicillin-resistant pathogens.…”
Section: Discussionsupporting
confidence: 49%
“…This suggests that there is a difference in the origin of the causative agent -community acquired or hospital acquired, which is more frequently described as a reason for increasing the health care-associated infections in relation to MRSA and MRSCoNS. 6,17,22 MLS resistance that did not correlate with hospital acquired infections. Moreover, a dramatic increase in clindamycin resistance among S. aureus isolates has been described.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Some studies have shown that S. aureus belonging to CC5 and CC30 are able to cause severe infections [16] with CC30 being associated with endocarditis, osteomyelitis and persistent bacteraemia [15]. CC8 strains were shown to be prone to cause persistence in endothelial cells [17]. CC45 strains form the predominant lineage in healthy individuals as well as bloodstream infections, particularly in the USA and Europe [18].…”
Section: Introductionmentioning
confidence: 99%